Short Communication: A new cyprinid fish Barilius cyanochlorus from Kerala, India - Dr. Mathews Plamoottil; K. VINEETH (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Plamoottil M, Vineeth K. 2020. Short Communication: A new cyprinid fish Barilius cyanochlorus from Kerala, India. Biodiversitas 21: 5389-5393. A new Barilius species is described from a small freshwater stream at Kasargod district of Kerala, India. It can be distinguished from its congeners in having a body with blackish-brown dorsal and upper laterals, greenish-yellow middle part and silvery lower lateral part, 8 vertical bands on mid-lateral region, each of these bands with 2 segments-lower blue part and upper green part, a large round blotch on the caudal base with similar color pattern, dorsal fin with basal 2/3 portion brown and distal 1/3 part orange-red, anal fin orange-red, pectoral fin pale reddish, 14-16 pre-dorsal scales and 37-39 lateral line scales. The new species is taxonomically analyzed, compared with its congeners, scientifically named and described. urn:lsid:zoobank.org:pub:F3B30158-CE71-496B-B8F4-B7645C2AD8B4  urn:lsid:zoobank.org:act:7763B3FE-6A97-447E-B718-2FB34807DFF9